Predictors of significant tricuspid regurgitation in atrial fibrillation: a meta-analysis - Zhang, Xiuxiu; Zhang, Na; Fu, Jia; Yu, Dapeng (Frontiers in Cardiovascular Medicine, 2025)
AimsSignificant tricuspid regurgitation (TR) in atrial fibrillation (AF) patients is becoming a global issue, as it can lead to progressive right ventricular enlargement and heart failure, thereby increasing morbidity and mortality. This study aimed to evaluate potential predictors of significant TR in AF patients using open databases.MethodsPubMed, EMBASE, the Cochrane Library, and Web of Science were searched for relevant studies from inception to September 2023. Using STATA 14.0 statistical software, hazard ratios (HRs) were calculated for data synthesis. The potential predictors included clinical characteristics, echocardiography parameters, and prior comorbidities. Evidence certainty was evaluated based on the GRADE system.ResultsIn total, 12 studies involving almost 16,000 patients were included in this review. Female sex (HR = 2.14; 95% CI: 1.84–2.49; I2 = 0.0%; p = 0.430), persistent atrial fibrillation (HR = 2.99; 95% CI: 2.47–3.61; I2 = 0.0%; p = 0.896), left ventricular ejection fraction [standard mean difference (SMD) = −0.16; 95% CI:−0.30 to −0.03; I2 = 69.8%; p < 0.000], age (HR = 1.07; 95% CI: 1.04–1.09; I2 = 72.3%; p = 0.013), heart failure (HR = 1.86; 95% CI: 1.45–2.39; I2 = 9.0%; p = 0.348), age ≥65 years (HR = 2.30; 95% CI: 1.63–3.25; I2 = 55.1%; p = 0.108), chronic lung disease (HR = 1.33; 95% CI: 1.02–1.74; I2 = 0.0%; p = 0.882), right ventricle fractional area change (SMD = 0.18; 95% CI: 0.01–0.36; I2 = 0.0%; p = 0.440), systolic pulmonary arterial pressure (SMD = 0.97; 95% CI: 0.76–1.19; I2 = 41.5%; p = 0.181), and proper ventricular systolic pressure (SMD = 1.07; 95% CI: 0.54–1.59; I2 = 92.4%; p < 0.000) may negatively influence significant TR.ConclusionsThis meta-analysis identified a potential negative influence of several clinical characteristics, echocardiography parameters, and previous comorbidities on significant TR. However, due to the low level of certainty of evidence, our analysis can only provide some guidance to practitioners and researchers. Caution is advised, and further validation is needed.